Organization of Testing in Distance Learning (on the base of Distance Learning System "Kherson Virtual University, 2.0"). - O. Gnedkova; D. Kravtsov (Kherson State University, 2009)
Descriptions of testing process and different types of test questions, which are realized in distance learning system «Kherson Virtual University, 2.0» are considered in the article.